2021
DOI: 10.3332/ecancer.2021.1168
|View full text |Cite
|
Sign up to set email alerts
|

Total neoadjuvant chemotherapy with FLOT scheme in resectable adenocarcinoma of the gastro-oesophageal junction or gastric adenocarcinoma: impact on pathological complete response and safety

Abstract: Background: Gastric cancer is the fifth cause of cancer incidence worldwide. Multidisciplinary approaches that improve the survival are needed. Perioperative chemotherapies show improvement in pathological complete remission (pCR) and overall survival (OS), but less than 50% of the patients completed the chemotherapeutic regimen. The recent 5-fluorouracil, leucovorin, oxaliplatin, docetaxel-4 (FLOT4) study shows OS 50 months and pCR 16.6%, but only 46% of the patients completed pre-and postoperative treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Taken together, our results in combination with other recently reported, support the ongoing continued evaluation of TNT in patients with locally advanced GE/G cancer using either FLOT or FOLFOX [28][29][30]. Given that rates of pCR are correlated with recurrence-free survival outcomes, the sum of our experience with FOLFIRINOX, FLOT, and FOLFOX in combination with those from recently reported studies suggests an early indicator that the TNT approach may be effective [25,26,28,31]. However, studies have yet to conclusively determine if survival outcomes can be improved with increased treatment intensity by delivering all chemotherapy prior to CRT and surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Taken together, our results in combination with other recently reported, support the ongoing continued evaluation of TNT in patients with locally advanced GE/G cancer using either FLOT or FOLFOX [28][29][30]. Given that rates of pCR are correlated with recurrence-free survival outcomes, the sum of our experience with FOLFIRINOX, FLOT, and FOLFOX in combination with those from recently reported studies suggests an early indicator that the TNT approach may be effective [25,26,28,31]. However, studies have yet to conclusively determine if survival outcomes can be improved with increased treatment intensity by delivering all chemotherapy prior to CRT and surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, 80% (20/25) underwent surgical resection, including 95% R0 resection and 28% pCR with acceptable rates of adverse effects. Taken together, our results in combination with other recently reported, support the ongoing continued evaluation of TNT in patients with locally advanced GE/G cancer using either FLOT or FOLFOX [28][29][30]. Given that rates of pCR are correlated with recurrence-free survival outcomes, the sum of our experience with FOLFIRINOX, FLOT, and FOLFOX in combination with those from recently reported studies suggests an early indicator that the TNT approach may be effective [25,26,28,31].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, OAC is an exemplar model of an obesity-driven cancer and as such its incidence is rapidly increasing in parallel with the rising level of obesity 2 . Response rates to the standard of care FLOT (5-fluorouracil (5-FU), oxaliplatin and docetaxel) chemotherapy regimen remain low with a complete pathologic response rate of 16.6% 3 and subsequent clinical outcomes are dismal with a median overall survival rate of 50 months 3 and 5-year overall survival rates as low as 15–40% depending on tumour stage at clinical presentation 4 . Improvements in the efficacy of first-line chemotherapy regimens were achieved through combining immune checkpoint blockade (ICB) with chemotherapy as depicted in the recent findings from the phase III Checkmate 649 trial, which demonstrated the synergy between nivolumab and first-line chemotherapy (FOLFOX and XELOX) in previously untreated oesophagogastric junctional adenocarcinoma (OGJ) patients (n = 1581), in which a significant improvement in overall survival in patients with a PD-L1 combined positive score of 5 or greater was observed (14.4 months (nivolumab plus chemotherapy arm) vs. 11.1 months (chemotherapy arm)) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported about the shorter survival of signet cell carcinoma in a neoadjuvant therapy setting. [22][23][24] Indeed, a further interesting subgroup analysis of our cohort showed that only patients with nonsignet cell carcinoma seemed to benefit from perioperative therapy with FLOT4 compared to 5FU/platinum derivative (p for log rank = .005). This benefit was not observed in patients with signet cell carcinoma (P = .375).…”
Section: Discussionmentioning
confidence: 81%